Asteroid observations at low phase angles. IV. Average parameters for the new H, G1, G2 magnitude system. (April 2016) - Shevchenko, Vasilij G.; Belskaya, Irina N.; Muinonen, Karri; Penttilä, Antti; Krugly, Yurij N.; Velichko, Feodor P.; Chiorny, Vasilij G.; Slyusarev, Ivan G.; Gaftonyuk, Ninel M.; Tereschenko, Igor A.
Abstract: We present new observational data for selected main-belt asteroids of different compositional types. The detailed magnitude–phase dependences including small phase angles (<1°) were obtained for these asteroids, namely: (10) Hygiea (down to the phase angle of 0.3°, C-type), (176) Iduna (0.2°, G-type), (214) Aschera (0.2°, E-type), (218) Bianca (0.3°, S-type), (250) Bettina (0.3°, M-type), (419) Aurelia (0.1°, F-type), (596) Scheila (0.2°, D-type), (635) Vundtia (0.2°, B-type), (671) Carnegia (0.2°, P-type), (717) Wisibada (0.1°, T-type), (1021) Flammario (0.6°, B-type), and (1279) Uganda (0.5°, E-type). For several asteroids, the dependences of brightness on the phase angle were investigated in the BVRI bands. We found a great diversity in the opposition-effect behavior both in the magnitude and the width of the opposition surges, especially for low-albedo asteroids. Some low-albedo asteroids (e.g., (10) Hygiea) display a broad opposition effect with an amplitude of 0.15–0.20 mag relative to the extrapolation of the linear part of the phase curve. Other asteroids (e.g., (596) Scheila, (1021) Flammario) show linear magnitude–phase dependences down to small phase angles (0.1–0.2°). Using numerous data sets on the magnitude–phase dependences with extensive phase-angle coverage, we examined in more detail the new three-parameter H, G 1, G 2 magnitude system. We determined the values of the G 1 and G 2 parameters for magnitude phase dependences of individual asteroids and obtained the average parameters for main asteroid compositional types. The values obtained can be used for the estimation of the absolute magnitude of an asteroid from a single observed magnitude when the magnitude–phase dependency is unknown and/or to calculate a visible magnitude for the ephemerides.